Analisis Desa Rogoselo dalam Perspektif Sejarah dan Cerita Rakyat dengan Melalui Pemanfaatan Potensi Wisata Religi (Studi di Desa Rogoselo Kecamatan Doro Kabupaten Pekalongan) - Hikmah Fitriyani; Atina Nur Amilah; Ahmad Hidayatullah (STAI Terpadu Yogyakarta, 2022)
Rogoselo Village is one of the villages in Pekalongan regency that has a direction of developing a tourist village, focusing on becoming a religious-based tourism village. The destination carried by Rogoselo Village with the existence of the Tomb of Ki Ageng Rogoselo and the Tomb of Ki Gede Penatas Angin. The atmosphere of the tourist village in Rogoselo Village has shown the typical atmosphere of a religiously themed tourist village. In addition, there is a bengkelung tour not far from Rogoselo Village. Bengkelung tourism was previously included in Rogoselo Village, and moved to Sidoharjo Village in Doro District, Pekalongan Regency a few years ago. The purpose of this study is to identify the development and utilization of religious tourism potential owned by Rogoselo Village. The method used in this study is to use qualitative descriptive methods. Data collection using direct interview techniques to community leaders or tomb caretakers and workshop administrators and tour owners. The results of the research that has been obtained that the development of Rogoselo Village through the use of religious tourism potential has a very big influence in it, one of which is improving the economy of the local community. But unfortunately, the local village government is still weak in terms of village development through religious tourism and natural tourism. In terms of management, it is quite good, it's just that the network of partners of this village is still limited in number. Finally, in an effort to promote tourism villages, managers already have a good capacity to produce promotional suggestions through print, electronic and internet media, but have not been supported by the ability to expand the tourist market to the archipelago to foreign countries.